SENYAWA FENOL PADA TOLERANSI Falcataria moluccana (Miq.) TERHADAP PENYAKIT KARAT TUMOR - Asri Insiana Putri; Mohammad Na'iem; Sapto Indrioko; Sri Rahayu (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2015)
Falcataria moluccana (Miq.) is severely attacked by Uromycladium tepperianum (Sacc.) McAlpine, which is a gall-forming (neoplasmic) and parasitic obligate pathogen. Phenolic compounds have the ability to function as co-factors of pathogenicity determinant of pathogens development and chemical defenses of plants. The purpose of this study was to determine the content of phenolic compounds on gall rust tolerance sengon by observation of tolerant sengon height, quantitative analysis of total phenolic compounds, wood anatomy analysis and tolerance test of sengon callus from tissue culture with filtrate gall rust as chemical agent. The results of the research were (1) inoculated sengon have lower total phenolic compounds than the control (no inoculation), (2) tolerant sengon have lower content of phenolic compounds than sensitive one, (3) microscopic wood anatomy observation shows that tolerant sengon have darker substrat, and (4) in the same concentration of gall rust filtrate incubation media, the tolerant sengon have higher survival cell calli. The highest concentration that callus cells can survive was 25% (v/v).